EDUKASI PENYAKIT KECACINGAN MELALUI MEDIA POSTER UNTUK MENINGKATKAN PENGETAHUAN SISWA SDN 14 TABING BANDA GADANG KECAMATAN NANGGALO KOTA PADANG - Syafrawati syafrawati; Mery Ramadani (BULETIN ILMIAH NAGARI MEMBANGUN, 2022)
The prevalence of helminthiasis worldwide for pre-school-age children is estimated at 267 million and for school-age children, it is estimated at 568 million. The risk factor for the high prevalence of helminthiasis is the low level of personal sanitation (clean and healthy lifestyle). The behavior referred to in children is often not washing hands before eating and after defecating, not keeping nails clean, and eating snacks in random places where cleanliness is not maintained. It is necessary to carry out counseling related to intestinal worms in elementary school children by teaching clean living behavior so that students can avoid helminthiasis. The method of activities carried out is in the form of health promotion using the lecture method (delivering prepared material) using poster media about what worms are, the characteristics of worms, and how to prevent worms. Before delivering the material, a pre-test was carried out and finally, a post-test was carried out to see changes in student knowledge. The activity was also accompanied by the handing out of deworming and other health posters to schools. It was found that after counseling there was a significant increase in student's knowledge of the material presented from an average score of 71 to 84. The conclusion was that the implementation of counseling using poster media increased students' knowledge about helminthiasis. It is recommended that schools can put posters in places that are easy for students to see and schools procure other posters related to disease prevention and implementing clean living behaviors..